2013
DOI: 10.1007/s00125-013-3147-y
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 1 activity in the developing human pancreas modulates retinoic acid signalling in mediating islet differentiation and survival

Abstract: Our findings indicate that ALDH1(+) cells represent a pool of endocrine precursors in the developing human pancreas and that ALDH1 activity is required during endocrine cell differentiation. Inhibition of ALDH1-mediated retinoid signalling impairs human fetal islet cell differentiation and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Previous research from our group and others have shown that high ALDH‐activity is a conserved function of multiple stem and progenitor cell lineages including endothelial precursors , mesenchymal stem cells , neural progenitors , muscle precursors , and pancreatic endocrine precursors among others (reviewed in ref. ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from our group and others have shown that high ALDH‐activity is a conserved function of multiple stem and progenitor cell lineages including endothelial precursors , mesenchymal stem cells , neural progenitors , muscle precursors , and pancreatic endocrine precursors among others (reviewed in ref. ).…”
Section: Discussionmentioning
confidence: 99%
“…As a major active metabolite of vitamin A (retinol), all-trans retinoic acid (RA) functions as a natural ligand for retinoic acid receptor and retinoid X receptor (RXR), nuclear hormone receptors that regulate the transcription of different kinds of genes controlling cell differentiation, embryonic development, and physiologic homeostasis (5,6). RA is an effective chemotherapeutic agent for acute promyelocytic leukemia for its transcriptional activation of RXRs (7)(8)(9).…”
Section: Nonalcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…23 Recently, the importance of ALDH1A1 for differentiating endocrine precursor cells in pancreas was reported. 24,25 In our cohort, ALDH1A1 expression was relatively homogeneous within individual insulinomas (instead of a 'stem cell' pattern), indicating an early clonal selection towards ALDH1A1-overexpressing cells in malignant insulinomas.…”
Section: Discussionmentioning
confidence: 75%